PENGARUH METODE MASSAGE EFFLURAGE TERHADAP PENGURANGAN INTENSITAS NYERI PADA PERSALINAN KALA I DI KLINIK MIMI SM. RAJA MEDAN TAHUN 2018 - NURHAMIDA FITHRI (Excellent Midwifery Journal, 2018)
ABSTRACTAll women experience pain during labor, this is a physiological process. One method that is very effective in overcoming it is by massage, namely the effleurage method and the method of abdominal lifting, which is one of the nonpharmacological methods carried out to reduce labor pain. Women who get the massage method during labor experience decreased anxiety, reduced pain, and significantly shorter labor times. The purpose of this risearch was to identify the effect of massage methods on reducing the intensity of pain in the first stage of labor before and after the intervention. This risearch uses a quasi-experimental design that is one group pretest-posttest. The number of samples in this risearch were 10 people. The data analysis used is the t-dependent, from the results of the t-dependent test, the intensity of the pain before the massage method effleurage averages 6.10 after the effleurage massage method is obtained, the average is 3.90. The average value of the difference in effleurage massage method is 2,200. Then it can be concluded that there is a significant difference between the intensity of pain before and after intervention (p value <0,0001). From the results of this risearch, it is known that the massage method is effective in reducing the intensity of pain in the first stage of labor. From the results of this risearch it was stated that the massage method can be used as an intervention in midwifery care for the mother. Keywords: Massage Method, Pain Intensity, First Stage of labor